Effect of sonication to the stability properties of carboxymethyl cellulose/uncaria gambir extract water-based lubricant - Dieter Rahmadiawan; Febrian Ilhamsyah; Hairul Abral; Imtiaz Ali Laghari; Yufrizal A (Universitas Negeri Padang, 2022)
This study examined the effect of sonication on FTIR and stability at various temperatures in water-based lubricants with a mixture of Carboxymethyl Cellulose (1wt%) and Uncaria Gambir extract (1wt% and 2wt%). The sample was prepared by mixing the two materials into distilled water using a magnetic stirrer and sonicator with time variations of 5 and 10 minutes. Before mixing, the Uncaria Gambir extract solution with water is first centrifuged to remove the dregs in the Uncaria Gambir extract powder. Stability was carried out in an open room (28oC), drying oven (50oC), and refrigerator (5oC). The stability test results showed that the mixture of Carboxymethyl Cellulose and Uncaria Gambir had good stability at all temperatures after sonication for a short duration. The longer sonication duration could fuse the fibrils of Carboxymethyl Cellulose, leading to increasing particle size. FTIR results also show that there is no chemical reaction that occurs. After adding the gambier, there was a new peak at wave 800-1300 cm-1, corresponding to the gambier. The results of this study indicate that the Carboxymethyl Cellulose and Uncaria Gambir solution can be a potential lubricant additive. The Carboxymethyl Cellulose can be a viscosity modifier, while Uncaria Gambir extract for corrosion inhibitor.